The development of graduate attributes: the Book of the Year project - Greenbaum, Lesley; Rycroft, Alan (South African Journal of Higher Education, 2016)
The notion of developing graduate attributes or generic skills through higher education, in order to enhance the employability of graduates, has become a focus of much attention in academic circles in the past decade. With the development of the key graduate skill of critical thinking in mind, a Book of the Year Project was introduced in 2012 at a South African Law Faculty. A questionnaire to ascertain a profile of the students was administered at the beginning of the project and a follow up survey to provide empirical data relating to the achievement of the objectives of the project was administered at the end of the first semester. An analysis of the data suggests that the project be continued. The authors conclude with some recommendations for future innovations related to such a project.